Formulation and Evaluation of Cream Using Moringa oleifera L. Leaf Extract - Gyawali, Rajendra; Bhattarai, Dinesh; Bartaula, Niraj; Bastola, Ramendra; Bhatta, Shantosh; Suwal, Srijana; Paudel, Prem Narayan (Journal of Institute of Science and Technology, 2022)
There are an increasing number of studies on the cosmeceutical properties of medicinal plants growing in various climatic zones. The formulation of phenolic rich plant extracts into cosmetic cream products can maximize the commercial value of such products. Most of the herbs used in Nepal for cosmetic purposes are locally available Ayurvedic herbs. The antioxidant property of the ethanolic extracts of Moringa oleifera L. leaves collected from Rupandehi and Makawanpur districts respectively were determined by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity. Total phenolic and total tannin content was determined by Foline Ciocalteu reagent. Total phenolic content was found from 35.51 and 42.89 mg/100 g gallic acid in the Makawanpur and Rupandehi districts. Overall, findings revealed that there were slight differences in antioxidant properties between the two samples. The cream formulated from the Makawanpur plant sample had considerable physiochemical parameters within the range of acceptance. These findings provide strong evidence for further development of commercial creams with antioxidant properties